1985
DOI: 10.3382/ps.0640852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Purified Aflatoxin on Broiler Chickens

Abstract: Purified aflatoxin B1 (AFB1) or AFB1 plus aflatoxin B2 (AFB2) was given daily for 5 weeks in gelatin capsules to 2-week-old feather-sexed broilers. In Experiment 1, pure AFB1 was given in doses equivalent to the quantity of toxin received, if diets containing either 0, 200, 500 or 1000 ppb of AFB1 were consumed. In Experiment 2, pure AFB1 or AFB1 plus B2 was administered in capsules in doses equivalent to the quantity of toxin received, if diets containing either 0, 100, 200, or 400 ppb of AFB1 were consumed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 11 publications
1
25
0
1
Order By: Relevance
“…However, those fed 500 ppb AFB, and 750 ppb AFB, were significantly lighter (P<0.05) than the controls (Table 2). These data agree with other reports (Giambrone et al, 1985a and1985b), in which a significant reduction in body weight in five-week-old broilers was observed only when fed a diet supplemented with at least 500 ppb AFB,.…”
Section: Body Weight Feed Consumption and Feed Conversionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, those fed 500 ppb AFB, and 750 ppb AFB, were significantly lighter (P<0.05) than the controls (Table 2). These data agree with other reports (Giambrone et al, 1985a and1985b), in which a significant reduction in body weight in five-week-old broilers was observed only when fed a diet supplemented with at least 500 ppb AFB,.…”
Section: Body Weight Feed Consumption and Feed Conversionsupporting
confidence: 82%
“…These data agree with those from previous studies in which the degree of immunosuppression was found to be directly related to the concentration of AFB, using the hemagglutinins produced in response to SRBC ("haxton et al, 1974). However, in another study using Pasteurella multocidu as the antigen, no significant reduction in antibody titer was observed when chicks were fed graded levels of AFB, (Giambrone et al, 1985a). Data collected in the present study indicate that AFB, at a dietary concentration of 250 ppb is a potent immunosuppressant in the broiler.…”
Section: Cutaneous Basophil Hypersensitivity Response and Antibody Timentioning
confidence: 54%
“…Aflatoxin has many adverse effects, of which immunotoxicity is one of the important toxicity reported in birds (Giambrone et al, 1985, Celik et al, 2000. Aflatoxin affects the immune organs mainly due to formation of DNA adduct in fast dividing lymphoid cells which leads to profound immunodeficiency by hampering the development and maturation of lymphoid organs (Dietert et al, 1985;Neldon-Ortiz and Qureshi, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Data of this research showed that AFB 1 levels as low as 200 ng/g could affect liver enzymes of broiler chicks. Giambrone (1985) showed that the development of acquarid immunity in turkeys and broilers was significantly when given 200 ng/g of pure AFB 1 capsules. According to Wogan (1974), dietary aflatoxin levels 100 ng/g induced liver carcinoma at an incidence greater than 50%, when feeding was continued up to 80 weeks.…”
Section: Resultsmentioning
confidence: 99%